A rigid redox-active-ligand-supported bis(germylene) as a two-centre six-electron donor. Issue 96 (15th November 2022) - Cui, Jingjing; Weiser, Jonas; Fantuzzi, Felipe; Dietz, Maximilian; Yatsenko, Yelyzaveta; Häfner, Andreas; Nees, Samuel; Krummenacher, Ivo; Zhang, Mingtao; Hammond, Kai; Roth, Paula; Lu, Wei; et al.
Abstract : A bis(germylene) based on a naphthyridinediamine (NDI) is reported. Calculations on the [NDI-Ge2 ][Fe2 (CO)6 ] complex revealed the six-electron donor behavior of NDI-Ge2, the first of its kind for bidentate ligands based on group 14 elements. Abstract : A naphthyridine diimine (NDI) supported bis(germylene) NDI-Ge2 containing two dicoordinate, coplanar Ge(ii ) atoms has been synthesised. Computational investigations on NDI-Ge2 indicated the two Ge(ii ) atoms are nearly independent. The EDA-NOCV analysis of the [NDI-Ge2 ][Fe2 (CO)6 ] complex revealed the six-electron donor behavior of NDI-Ge2, the first example for group-14-element-based bidentate ligands.